OPTICAL ACTIVITY OF PETROLEUM AND GAS-CONDENSATES AS A CRITERION OF THEIR ORIGIN - Kropotkin P.N. (My University, 1989)
It has long been thought that optical activity is exhibited only by organic compounds of biological origin, among which levorotatory forms are strongly predominant. Systematization of numerous data on the sign of the optical activity of oils indicates that levorotatory petroleums make up a maximum of 0.5 percent of the total number of petroleums that are optically active. If we accept the hypothesis that petroleum is of organic origin, we would have to believe that when biogenic matter is converted into petroleum or gas-condensate, for some reason levorotation is always, or almost always, converted to dextrorotation. Such a rearrangement of organic molecules may occur in some cases but a systematic pattern of this kind can hardly be accepted at the current level of development of organic chemistry.